How to comply with environmental regulations? The role of information - Botelho, Anabela (2003)
The effectiveness of environmental regulation can be viewed as conditioned by the action of at least two main agents: the regulated firms and the public agency (the regulator). The agency’s role is, on one hand, to enact environmental regulations and, on the other, to monitor firms’ environmental behavior and enforce environmental regulations. The regulated firms, on the other hand, must be informed about the legal limits imposed on them and subsequently they must be able to comply with those limits. Using a questionnaire on the pulp and paper industry in Portugal we found that firms decision to comply with environmental regulations is strongly influenced by firms’ information on its legal obligations and that this effect is stronger for smaller firms. Moreover larger and younger firms are less likely to comply with environmental regulations than smaller and older firms. With respect to the public agency’s behavior, we found that greater monitoring efforts are directed towards larger and younger firms, as well as towards those firms most likely to cause higher pollution levels.